The Conceptual Model of Enterprises’ Value Migration - Dariusz Siudak (Polityki Europejskie, Finanse i Marketing)
The goal of this article is to conceptualize the process of value migration between companies. It takes advantage of A. Slywotzky’s three stages of value migration model, which specifies the inflow, stability and outflow stages of value migration. The key issue is the discrimination of frames of the stability stage in terms of the volume of value migration as well as its timing.